2020
DOI: 10.1111/jcmm.15969
|View full text |Cite
|
Sign up to set email alerts
|

Calhex231 ameliorates myocardial fibrosis post myocardial infarction in rats through the autophagy‐NLRP3 inflammasome pathway in macrophages

Abstract: The calcium‐sensing receptor (CaSR) is involved in the pathophysiology of many cardiovascular diseases, including myocardial infarction (MI) and hypertension. The role of Calhex231, a specific inhibitor of CaSR, in myocardial fibrosis following MI is still unclear. Using Wistar rats, we investigated whether Calhex231 ameliorates myocardial fibrosis through the autophagy‐NLRP3 inflammasome pathway in macrophages post myocardial infarction (MI). The rats were randomly divided into sham, MI and MI + Calhex231 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Additionally, further experimentation revealed that treatment with sh-RBP-J also brought about a decrease in collagen content and degree of fibrosis, which is particularly important as macrophages are heralded as highly significant in the process of fibrosis ( 23 ). Interestingly, there is a plethora of evidence to suggest the involvement of macrophages in MI, such that macrophage polarization is regarded as critical to cardiac remodeling after MI in humans ( 4 , 6 ). Moreover, an insufficiency of macrophages was previously associated with impaired wound healing and promoted left ventricular remodeling after the occurrence of MI ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, further experimentation revealed that treatment with sh-RBP-J also brought about a decrease in collagen content and degree of fibrosis, which is particularly important as macrophages are heralded as highly significant in the process of fibrosis ( 23 ). Interestingly, there is a plethora of evidence to suggest the involvement of macrophages in MI, such that macrophage polarization is regarded as critical to cardiac remodeling after MI in humans ( 4 , 6 ). Moreover, an insufficiency of macrophages was previously associated with impaired wound healing and promoted left ventricular remodeling after the occurrence of MI ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence to suggest that M2 macrophages can suppress extracellular matrix synthesis and inflammatory responses in the process of tissue repair ( 26 ). Meanwhile, Liu et al recently demonstrated that Calhex231 can improve myocardial fibrosis after MI by regulating the autophagy-NLRP3 pathway in macrophages ( 4 ). Altogether, the aforementioned evidence supported our results such that blockade of Notch signaling exerts a reductive effect on cardiac inflammation and that Notch signaling-mediated macrophage polarization can regulate fibrosis by affecting the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Calhex231 may ameliorate myocardial fibrosis by inhibiting autophagymediated activation of NLRP3 inflammasome. 26 However, extensive validation is needed to improve our understanding of autophagy in the pathogenesis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction (MI) is one of the most prevailing lethal diseases around the world, characterized by inadequate cardiac blood supply, typically developing into myocardial brosis [1][2][3] . MI triggers mass death of cardiomyocyte through necrosis or apoptosis, leading to the reduction of cardiomyocyte number 4,5 .…”
Section: Introductionmentioning
confidence: 99%